New insights into the mechanical and self-healing properties of polymers cross-linked by Fe(iii)-2, 6-pyridinedicarboxamide coordination complexes. Issue 3 (6th December 2018) - Mo, Sheng-Ran; Lai, Jian-Cheng; Zeng, Ke-Yu; Wang, Da-Peng; Li, Cheng-Hui; Zuo, Jing-Lin
Abstract : Distinct mechanical and self-healing properties are observed in two PBCA polymers cross-linked by the mono-deprotonated complex [Fe(Hpdca)] + and the double-deprotonated complex [Fe(pdca)] − . Abstract : In order to understand the mechanical and self-healing properties of polymers cross-linked by Fe(iii )-2, 6-pyridinedicarboxamide (pdca) coordination complexes, herein we performed the reaction between 2, 6-pyridinedicarboxamide and FeCl3 under both neutral and alkaline conditions, and studied the dynamic ligand exchange properties of the resulting model complexes. The results showed that [Fe(Hpdca)] + exhibited a rapid ligand exchange property which was not observed for [Fe(pdca)] − . Correspondingly, polymer Fe-Hpdca-PBCA (PBCA = poly(butadiene- co -acrylonitrile)) was weak, highly stretchable and self-healable, while Fe-pdca-PBCA was strong and poorly stretchable and can only be partially healed with a prolonged time. These results deliver a clear indication of the important impact of the bond strength and dynamics of coordination complexes on the mechanical and self-healing properties of polymers. Such an understanding is helpful for further design of novel synthetic polymers which can achieve an optimal balance between the mechanical strength and self-healing performance.